The Influence Of Convenience And Risk Perception On Interest In Using The Akulaku Online Loan Application In The Community Of Seluma South District - Putra, Edo Agus; Irwanto, Tito; Putra, Iswidana Utama (Journal of Management, Economic, and Accounting, 2024)
The aim of this research is to determine the influence of risk perception on interest in using the Akulaku online loan application in the South Seluma District community. The sample in this study was 60 people from South Seluma District who had made online loans on the Akulaku application. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the analysis show that convenience has a significant effect on interest in using the Akulaku online loan application among the people of South Seluma District, this is proven by the results of the t test showing the tcount value is greater than ttable (3.246 > 1.671) and a significant value of 0.002 < 0.05b meaning H_0 rejected and H_a accepted. Risk perception has a significant influence on interest in using the Akulaku online loan application among the people of South Seluma District, this is proven by the results of the t test showing that the t value is greater than t table (3.727 > 1.671) with a significant value of 0.000 < 0.05 meaning H_0 is rejected and H_a accepted. Convenience (X_1) and perceived risk (X_2) together have a significant effect on consumers' interest in using online loan applications (Y) in South Seluma District, this is proven by the F test showing the value of Fcount > Ftable (21.311 > 3.16) with a significant value of 0.000.